Pengolahan Limbah Organik Pasar Menggunakan Reaktor Cacing Tanah (Lumbricus rubellus) dengan Metode Continuous Flow Bin - Mashur Mashur; Hunaepi Hunaepi; Kemas Usman; Iwan Desimal (Bioscientist : Jurnal Ilmiah Biologi, 2020)
Market waste is the second largest waste after household waste. Vegetable and fruit waste is the largest organic waste that comes from market waste. Various waste management efforts have been carried out by the government and the community, but have not completely resolved the waste problem. The purpose of this study was to determine the effect of market organic waste processing using an earthworm reactor (Lumbricus rubellus) with a modified Continuous Flow Bin method on cocoon production, biomass, and exmecat. This study used an experimental method with a completely randomized design (CRD), with three treatments of a continuous flow bin modified three types of mixed media materials to increase cocoon production, biomass, and exmecat quality. The results showed that the type of reactor had a significant effect (P ≤ 0.05) on cocoon production, the amount of biomass, biomass weight, broodstock mortality, exmecat production, media temperature, and media humidity, but had no effect on media pH. The use of reactor 2 (R2) with a mixture of 50% horse feces + 50% rice straw + feed 50 grams / day / nest box for market organic waste is the best reactor compared to reactor 1 (R1) and reactor 3 (R3). The amount of organic waste that can be processed by earthworms (Lumbricus rubellus) either as a medium or as feed is an average of 4.35 kg / nest box for 40 days of cultivation with a stocking density of 25 grams of earthworms / nest box. Based on the results of this study, it can be concluded that the ability of earthworms (Lumbricus rubellus) to process market organic waste using the modified Continuous Flow Bin method can reach 4.35 times their body weight / day. Thus, this waste processing method can be a complete solution to solving market organic waste management problems.